Opioid Shopping Behavior: How Often, How Soon, Which Drugs, and What Payment Method. (24th January 2013) - Cepeda, M. Soledad; Fife, Daniel; Chow, Wing; Mastrogiovanni, Gregory; Henderson, Scott C.
Abstract Doctor shopping (obtaining opioid prescriptions from multiple prescribers) is one example of opioid abuse and diversion. The authors assessed how soon shopping behavior was observed after opioid exposure, number of events per shopper, preferred opioids, and method of payment. This was a cohort study. Individuals with ≤1 dispensing for any opioid in 2008 were followed for 18 months. Shopping behavior was defined as ≤2 prescriptions by different prescribers with ≤1 day of overlap and filled at ≤3 pharmacies. Of 25, 161, 024 subjects, 0.30% exhibited shopping behavior. Opioid‐experienced subjects were 13.7 times more likely to exhibit shopping behavior and had more shopping episodes than opioid‐naive subjects. Time to first shopping event was 246.90 ± 163.61 days. Number of episodes was 2.74 ± 4.66. Most subjects with shopping behavior (55.27%) had 1 shopping episode, whereas 9.52% had ≤6 episodes; 88.99% had ≤4 prescribers. Subjects with shopping behavior filled schedule II opioids more often than subjects without shopping behavior (19.51% vs 10.89%) and more often paid in cash (44.85% vs 18.54%). Three of 1000 people exposed to opioids exhibit shopping behavior, on average, 8 months after exposure. Opioid shoppers seek strong opioids, avoid combination products, often pay cash, and obtain prescriptions from few prescribers.